Endoscopic versus laparoscopic treatment for choledocholithiasis: a prospective randomized controlled trial - Barreras González, Javier Ernesto; Torres Peña, Rafael; Ruiz Torres, Julián; Martínez Alfonso, Miguel Ángel; Brizuela Quintanilla, Raúl; Morera Pérez, Maricela (Endoscopy International Open, 2016)
Background and study aims: Overall, 5 % to 15 % of patients undergoing cholecystectomy for cholelithiasis have concomitant bile duct stones, and the incidence of choledocholithiasis increases with age. There is no clear consensus on the best therapeutic approach (endoscopic versus surgical). Patients and methods: A prospective randomized controlled clinical trial was performed to compare three treatment options for patients with choledocholithiasis at the National Center for Minimally Invasive Surgery in Havana, Cuba from November 2007 to November 2011. The patients were randomized in three groups. Group I: patients who underwent intraoperative cholangiography (IOC) to confirm the choledocholithiasis followed by laparoscopic cholecystectomy (LC) associated with intraoperative endoscopic retrograde cholangiopancreatography (ERCP), group II: patients who underwent preoperative ERCP followed by LC during the same hospital admission and group III: patients who underwent IOC to confirm the choledocholithiasis followed by LC associated with laparoscopic common bile duct exploration (LCBDE). Results: A total of 300 patients with suspected choledocholithiasis were included in the trial and were randomized. As a result, a total of 134 patients were diagnosed with the presence of choledocholithiasis and treated during the study period. There were no significant differences in success rates of ductal stone clearance, but retained stone, postoperative complications and length of hospital stay were better in group I.Conclusions: Intraoperative ERCP/ES shows a higher rate of common bile duct stones clearance, a shorter hospital stay, and lower morbidity, but further research with a larger study population is necessary to determine the additional benefits of this procedure. The results to date suggests that in appropriate patients, single-stage treatments are the best options.